An Example of an Activity Developed in Accordance with the 5E Learning Model for Teaching Solutions - Samih Bayrakçeken; İclal Avinç Akpınar (Üniversite Araştırmaları Dergisi)
In today’s life, individuals are forced to be a constant learner to ensure their development. It is necessary to save the act of learning from rote learning, to gain the ability to think independently, and to raise individuals who learn by understanding. In this study, it is aimed to develop and present an active learning activity example prepared to be used at various levels of science teaching. In order for learners to achieve this goal, effective student-centered methods and techniques are needed. 5E model is one of them. In this study, activities related to the subject of solutions were developed, implemented, evaluated and necessary corrections were made in accordance with the 5E learning model. In this study, concept achievement test and semi-structured interview were used as data collection tools and both qualitative and quantitative data collection tools were used together to provide data diversity. In the analysis of quantitative results, t-test and MANOVA model were used, and in the analysis of qualitative data, the interviews with the students were transcribed. The results showed that the experimental groups were more successful than the control groups in terms of concept achievement in the subject of solutions after the application.